Comparación de viabilidad de exportación colombiana de manufacturas fabricadas entre cuero genuino y cuero vegetal derivado de la palma de piña hacia Alemania (2023)
The purpose of this research study is to demonstrate the viability of Colombian exports of manufactures made between genuine leather and vegetable leather derived from the pineapple palm to Germany. Where the growth in the vegetable leather sector at an industrial level increasingly maintains a variation in the quality of production